Shit happens – a glimpse into males’ mating tactics in a polygynous ungulate - the reindeer - Holand, Øystein; L’Italien, Léon; Weladji, Robert B.; Djaković, Natasa; Røed, Knut; Hovland, Anne Lene; Nieminen, Mauri (Rangifer, 2012)
This is about the two big "guys", Spot and Mika, and their endeavour to propagate their genes during the mating season 2007. They were 6 and 5 years old weighting 172 and 141 kg before rut, respectively. Together with 23 other males (one 5 yrs, two 4 yrs, three 3 yrs, six 2 yrs and eleven 1 yr old) they roamed within a 15 km2 fenced area competing for access to 87 females. Indeed, the competition was intense and all males present contributed to the dynamic observed. Especially Hot, the heaviest 4 yrs old male weighing 155 kg before rut, played a prominent role - in addition to Spot and Mika, their mating tactics being highly dynamic. However there is no short cut to success - strength have to be coupled with smartness - but shit happens - as we'll see.